Aberrant PRDM2 methylation as an early event in serrated lesions destined to evolve into microsatellite‐instable colorectal cancers - David EFWM vanToledo; Arne GC Bleijenberg; Andrea Venema; Mireille J deWit; Susanne vanEeden; Gerrit A Meijer; Beatrice Carvalho; Evelien Dekker; Peter Henneman; Joep EG IJspeert; Carel JM vanNoesel (Wiley, 2024)
Abstract Up to 30% of colorectal cancers (CRCs) develop from sessile serrated lesions (SSLs). Within the serrated neoplasia pathway, at least two principally distinct oncogenetic routes exist generating microsatellite‐stable and microsatellite‐instable CRCs, respectively. Aberrant DNA methylation (DNAm) is found early in the serrated pathway and might play a role in both oncogenetic routes. We studied a cohort of 23 SSLs with a small focus (<10 mm) of dysplasia or cancer, 10 of which were MLH1 deficient and 13 MLH1 proficient. By comparing, for each SSL, the methylation status of (1) the region of dysplasia or cancer (SSL‐D), (2) the nondysplastic SSL (SSL), and (3) adjacent normal mucosa, differentially methylated probes (DMPs) and regions (DMRs) were assessed both genome‐wide as well as in a tumor‐suppressor gene‐focused approach. By comparing DNAm of MLH1‐deficient SSL‐Ds with their corresponding SSLs, we identified five DMRs, including those annotating for PRDM2 and, not unexpectedly, MLH1. PRDM2 gene promotor methylation was associated with MLH1 expression status, as it was largely hypermethylated in MLH1‐deficient SSL‐Ds and hypomethylated in MLH1‐proficient SSL‐Ds. Significantly increased DNAm levels of PRDM2 and MLH1, in particular at 'critical' MLH1 probe sites, were to some extent already visible in SSLs as compared to normal mucosa (p = 0.02, p = 0.01, p < 0.0001, respectively). No DMRs, nor DMPs, were identified for SSLs destined to evolve into MLH1‐proficient SSL‐Ds. Our data indicate that, within both arms of the serrated CRC pathway, the majority of the epigenetic alterations are introduced early during SSL formation. Promoter hypermethylation of PRDM2 and MLH1 on the other hand specifically initiates in SSLs destined to transform into MLH1‐deficient CRCs suggesting that the fate of SSLs may not necessarily result from a stochastic process but possibly is already imprinted and predisposed.